A preliminary Study on the Effect of Head and Neck Chemoradiotherapy on Systematic Immunity. Issue 4 (25th October 2019) - Huang, Weiqiang; Fan, Yao; Cheng, Xiaoya; Liang, Huazhen; Pan, Hua; Xiao, Ting; Chen, Min; Guan, Jian
Background: This study was designed initially to explore the effect of chemoradiotherapy on patients diagnosed with head and neck cancer (HNC) with respect to the alteration of systematic immunity. Methods: We did a retrospective study enrolling patients received concurrent chemoradiotherapy (CCRT), with or without induction chemotherapy (IC). Blood tests were performed before IC, before and after CCRT. Flow cytometric analysis and turbidimetric inhibition immunoassay were used for detection. Results: A total number of 58 patients were included from April 1, 2018, to March 31, 2019. Levels of immunoglobulins (Ig), including IgA, IgG, and IgM, declined after 2 to 3 cycles of IC and CCRT, respectively. Serum level of total hemolytic complement (CH50) increased ( P < .001) after IC, but kept stably post-CCRT. Natural killer (NK) cells decreased ( P < .01) after IC and enhanced ( P < .001) post-CCRT. The number of CD3 + CD4 + T cells got increased ( P < .01) after IC and decreased ( P < .001) post-CCRT. Consistently, both IC and CCRT induced the increase in CD3 + CD8 + T cells significantly ( P < .001 vs P < .01). Conclusion: Both radiotherapy (RT) and chemotherapy (CT) induced dual effect of immune response. Concurrent chemoradiotherapy created an active immune response based on the effect induced by IC, suggesting that RT exerted a potential function on mobilizing immune system.